Emotional intelligence in action: theoretical models for educators to enhance learning and connection in the classroom: a conceptual review - Matjie, Mokgata Alleen (Frontiers in Psychology, 2025)
Emotional quotient (EQ) and emotional intelligence (EI) are often conflated with cognitive intelligence (CI); however, it distinctly refers to the quantifiable assessment of an individual’s emotional competencies and capabilities. A higher EQ is typically indicative of greater emotional proficiency, which is essential for various professionals, including educators, so that they can effectively tap into the CI of learners when teaching. Effective teaching transcends mere knowledge transfer; it necessitates the ability to connect emotionally with learners to foster an engaging and supportive educational environment. Unfortunately, many educators may not be cognizant of types of intelligences and learning styles and what these skills can contribute to their teaching efficacy, more specifically the emotional intelligence (EI). A successful educational interaction demands qualities such as compassion and patience, which help bridge the emotional gap between educators and learners. Thus, the cultivation of EI in educators can significantly enhance their ability to connect with diverse learners using different learning styles and intelligences, as well as other relevant theories. Professional development programs that focus on upskilling educators on the learning styles and intelligences, especially the EI and CI, can empower educators, equipping them with the necessary tools to leverage their emotional skills in the classroom for improved learning outcomes.